Synthesis and Electrochemical Properties of SnO2 Composited Activated Carbon from Coffee Ground Waste for Supercapacitor Applications - Agung Nugroho; Muhammad Reza Wirayudha Pratama; Hans Kristianto; Haryo Satriya Oktaviano; Arenst Andreas Arie; Ratna Frida Susanti (Jurnal Kimia Sains dan Aplikasi, 2023)
Biomass has been considered an alternative source of electrode materials. Converting biomass into activated carbon is one of the possible approaches. Coffee ground waste is abundant as the world’s coffee-drinking culture grows. This paper describes a study that converted coffee grounds into activated carbon and tested its feasibility for electrode materials. We use a simple pyrolysis technique (800°C) to synthesize activated carbon from waste coffee grounds, with potassium hydroxide (KOH) as an activator. Tin oxide (SnO2), which has a high theoretical capacity, was impregnated into the carbon framework using a hydrothermal method operating at 180°C for 2 hours. The X-ray diffraction (XRD) pattern and Fourier transform infrared spectroscopy (FTIR) results show that SnO2 was successfully impregnated into the carbon structure. Raman analysis also shows that the carbon structure of the activated carbon still retains despite the presence of the metal oxide during the hydrothermal synthesis. Furthermore, electrochemical measurements utilizing the galvanostatic method using a three-electrode system demonstrated that the specific capacitance of the material increased by approximately 106% at 5 A/g following SnO2 impregnation. Long cycle testing further demonstrates that including SnO2 in the carbon, structure may sustain outstanding performance even at high current densities of 5 A/g for 100 cycles with 99% capacity retention. The results demonstrate the possibility of activated carbon from coffee ground waste composited with tin oxide as supercapacitor electrodes.